Political Economy of Energy Pipelines in Central Asia and Caucasus - Hadi Ajili; Mohammad Reza Bahador Khani (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2015)
Abstract Central Asia and Caucasus has been a core of concentration for great powers for a long time. In Soviet Union era, due to the Russia’s domination on the region foreign access was limited. After the collapse of Soviet Union and independence of Central Asia and Caucasian countries, the gap provided opportunity for other powers. Oil and gas has always been a reason for the presence of other countries in this region. Dire security situation of the region and limited access to the open sees raise a question about rationality of involvement in energy sector of the region. The hypothesis of this paper argues that political measures overwhelmed economic and security concerns for foreign energy investors in this region.